Evaluation and classification of different types of anthropogenic resources: the cases of old landfills, obsolete computers and in-use wind turbines. (1st October 2016) - Winterstetter, A.; Laner, D.; Rechberger, H.; Fellner, J.
Abstract: Various recent policy initiatives indicate an increasing need for a comprehensive overview of potentially extractable anthropogenic resources, in order to compare them with geogenic resources. Therefore, a method has been developed to evaluate and classify anthropogenic resource deposits and to prioritize potential extraction projects in a transparent manner. In this study we present how anthropogenic resources can be systematically integrated into the United Nations Framework Classification for Fossil Energy and Mineral Reserves and Resources 2009 (UNFC-2009). The main goal is to illustrate different settings of anthropogenic resource classification, and to provide specific criteria to map different types of anthropogenic resources within the three dimensions of UNFC-2009, i.e. "knowledge on composition and extractable material content", "technical and project feasibility" and "socioeconomic viability". Projects for recovering materials from an old landfill, from obsolete PCs (personal computers), and from in-use wind turbines are exemplarily evaluated and classified under UNFC-2009. The economic results depend on the respective scenarios, where the timing of mining is varied, different organizational and societal settings are compared and different choices for technological options are made. While landfill mining under current conditions is not economically viable, the final result might look different in the future with changing key modifying factors, such as increasing secondary raw material prices. Mining materials from obsolete PCs and from permanent magnets in in-use wind turbines would both yield positive economic results for all investigated scenarios. Graphical abstract: Highlights: A new evaluation procedure in line with the classification system UNFC-2009 is applied to anthropogenic resources. Influencing factors differ for anthropogenic in-use stocks, obsolete stocks and waste flows. The resource potentials of an old landfill, obsolete PCs and in-use wind turbines are evaluated and compared. Specific criteria for the classification of anthropogenic resources under UNFC-2009 are developed.